PENGARUH NILAI TUKAR RUPIAH DAN BI 7 DAYS REPO RATE TERHADAP INDEKS SAHAM SYARIAH INDONESIA (PERIODE 2016-2019) - Panji Ahmad Khairulanam; Parno Parno; Angrum Pratiwi; Tika Parlina (Fakultas Ekonomi dan Bisnis Islam Universitas Islam Negeri Sultan Aji Muhammad Idris Samarinda, 2021)
This study has the background that the capital market has an important role in the economy of a country because the capital market performs two functions, namely as a means for business funding or as a means for companies to obtain funds from the investor community. Second, the two capital markets become a means for people to invest in financial instruments such as stocks, bonds, mutual funds and so on. Thus the community can place funds in accordance with the profit and risk characteristics of each instrument.there are several macroeconomic and monetary factors that can affect stock movements such as the rupiah exchange rate and BI 7 days repo rate. This study aims to determine the effect of the Rupiah and BI 7 Days Repo Rate on the Indonesian sharia stock indekx in the (2016-2019 Period) partially or simultaneously. The research method used in this study is a quantitative method. The object of this research is a statistical report on Indonesian Islamic stock indexes operating in Indonesia and registered in sharia capital market statistics issued by the Financial Services Authority and obtained from the official website of Bank Indonesia (BI). The analytical method used in this study is multiple regression analysis. The results of this study indicate that partially the rupiah exchange rate has a significant positive effect on the Indonesian Islamic stock index and the BI 7 days repo rate has a significant negative effect on the Indonesian Islamic stock index. While simultaneously the rupiah exchange rate variable and the BI 7 days repo rate have a significant positive effect on the Indonesian sharia stock index.